`I was really, really shocked`: A sociological exploration of the transition experiences of English Youth Academy male footballers from school to work - Hague, N.; Law, G. (International Review for the Sociology of Sport, 2022)
The world of football arguably brings together and unites people in support of their teams and countries, while inspiring young children and adolescents to dream of a professional career. Existing research in the field has sought to begin to understand what professional footballers experience on their journey through the game. However, much of this UK-based research has focused on first team players and their professional experiences, including transitions from youth team to first team and to retirement. This study, therefore, aimed to examine players during their youth academy scholarship at one English Championship club. This study focused on the transitional experiences of youth players from school to the academy and their resulting embodying of a footballer`s identity. Twelve semi-structured interviews with players aged 17-19, were conducted and then analysed by thematic analysis using figurational sociology concepts. Three different types of transition were identified. Among other reasons, early specialisation in football was a prevalent factor that partly influenced the way the players experienced their transition. The transition into the academy coincided with the transition from youth to adulthood that was arguably anything but linear as players managed the dominant sub-cultures present in the club.